Open transcatheter aortic valve implantation on a degenerated bioprosthetic valve conduit. Issue 9 (15th September 2018) - Elghannam, Mahmoud; Haldenwang, Peter-Lukas; Aljabery, Yazan; Moustafine, Vadim; Strauch, Justus
Abstract: The degeneration of bioprosthetic aortic Conduit with hemodynamic dysfunction mostly requires a re-do surgery, which is associated with an increased perioperative risk. Considering this, an open implantation of a transcatheter aortic bioprothesis (TAVI) after resection of the degenerated valve leaflets could be of great benefit, reducing cross-clamp and cardiopulmonary bypass duration, especially in combined surgery in high-risk patients. This is a case of a high-risk female (78 years, EuroScore 59%) treated with an open TAVI as an alternative to conventional valve or aortic conduit replacement for degenerative aortic valve due to endocarditis lente, 2 years following a bio-Bentall procedure.